RECURSOS TECNOLÓGICOS EN EL AULA Y SU IMPACTO EN EL APRENDIZAJE DE LOS ESTUDIANTES DEL SEXTO AÑO EGB EN LA UEF SIMÓN BOLÍVAR - MACIAS ARROYO MARIT MARIAN (2024)
In recent years, technological resources have gained a place in most contexts of society and around the planet the use of tablets, digital whiteboards, computers and various electronic devices that energize, innovate and make Learning becomes an interesting process. From this perspective, a digital world is offered through the Internet with a lot of information available to students, making learning universal and quality, in addition to the development of digital skills that are important today, which is why this case study called technological resources in the classroom and their impact on the learning of sixth-year EGB students at the UEF Simón Bolívar's general objective is to determine the impact of technological resources in the classroom on the learning of sixth-year EGB students at the Unit Simón Bolívar Fiscomisional Educational. Because it was a case study, it required a qualitative research methodology in order to collect information based on experiences, perspectives and ideas. The level of research used is descriptive and the main source of information is documentary, involving the critical review and systematic analysis of relevant and pertinent documentary sources. As a research technique, the interview was implemented to collect information about the problem and as an instrument, the questionnaire with 5 questions was used to address key aspects of the research.